Qualitative text analysis : a guide to methods, practice and using software - Kuckartz, Udo , 1951- (SAGE, 2014)
Providing students and researchers with a guide to systematic analysis, with an emphasis on using software, this is a hands-on introduction to the central steps involved with qualitative analysis